An Overview to Candidiasis: Types of Candidiasis, Virulence Factors, Symptoms of Infection and Treatment - Al-Garawi, Noor Alhouda D.; Suhail, Ammar A.; Meri, Marwa Ahmed (Medical Science Journal for Advance Research, 2022)
Candida is a kind of yeast, is a fungus that infects the body.Candidiasis is known as yeast contagion because the infecting agent is a yeast, Candida albicans. Candida albicans are the pathogens that are of much significance which are present everywhere and mostly reside along side plentiful bacteria near mouth, gastrointestinal tract and vagina. Hippocrates was the first person to describe candidiasis in 1849. Candidiasis of the mouth is termed as Thrush. Cutaneous candidiasis is a skin infection that occurs in parts of the skin that have very little ventilation and are rarely moist. Deep Candidiasis occurs when fungi infiltrate the body, enter the bloodstream, and spread throughout the body.Treatment methodology are different for each case. Natural prevention is mandatory to safe yourself from being a victim to disease